2015
DOI: 10.1089/tmj.2014.0095
|View full text |Cite
|
Sign up to set email alerts
|

A Web Application for Self-Monitoring Improves Symptoms in Chronic Systolic Heart Failure

Abstract: A Web application for self-monitoring heart failure over 12 weeks improved both NYHA classification and MLHFQ score. The trend in improved physical activity and physical exam support these outcomes. The number of patients reporting a sodium-restricted diet increased over the 12 weeks, which may have led to the positive findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Evaluative research in this area has found a mixed picture in terms of the impact of patient monitoring on self-management and patient outcomes. 313,318,[372][373][374][375] Mixed-methods research is needed to explore the contexts in which and mechanisms through which these interventions achieve their intended outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Evaluative research in this area has found a mixed picture in terms of the impact of patient monitoring on self-management and patient outcomes. 313,318,[372][373][374][375] Mixed-methods research is needed to explore the contexts in which and mechanisms through which these interventions achieve their intended outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…In the vast scientific literature on telemedicine systems, we have found only a few reports of systems that use data and information coming directly from patients [ 22 - 27 ], although several systems, as for example Philips’ eCareCompanion and eCareCoordinator [ 28 ], are now moving on to collecting this information through tablets or smartphones [ 29 , 30 ]. Surely researchers are exploring the implications of how and when these subjective data are collected, their utility for effective monitoring, and, more relevant from our point of view, whether there is a quality control process for this subjective information and how it works, but results have not reached the publication stage.…”
Section: Introductionmentioning
confidence: 99%
“…15 Combining body observation, body analysis and informal caregivers' involvement to support symptom perception Body observation (ie, body listening, symptom monitoring) and body analysis (ie, symptom recognition, interpretation and labelling) are crucial elements to combine to support symptom perception. According to a literature review, 14 seven interventions [33][34][35][36][37][38][39] targeting symptom perception in pilot studies have shown promising results in terms of clinical improvement of HF self-care, 33 34 decreased symptom intensity, 35 number of symptoms 36 and perceived distress 33 as well as better health-related quality of life. 35 36 Another study 40 focusing on symptom perception and symptom response pilot-tested the efficacy of a similar training programme and reported greater absolute change compared with controls for self-care maintenance and confidence.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%